Pengaruh Literasi Keuangan dan Motivasi Investasi terhadap Minat Berinvestasi Mahasiswa di Kota Cimahi - Nurhaliza, Rahma; Simatupang, Frido Saritua (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the influence of financial literacy and investment motivation on interest in investing in Cimahi City. The research method used is a quantitative method. The population in this study were all students who live in Cimahi City. The sampling technique in this research was non-probability sampling using the G-Power tool and obtained a sample size of 107 respondents. Multiple regression analysis was used, so the research results revealed that simultaneously and partially financial literacy and investment motivation had a significant and positive effect on students' investment interest in Cimahi City.